Characteristics of Corn Cob Cellulose Based Bioplastics as Active Packaging for Pempek (Traditional Fish Cake) Products - Pridata Gina Putri; Nurma Pratiwi; Fahrulsyah; Taufik Nugraha Agassi; Deary Amethy Zahrotinufus (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
The high level of corn production in Lampung Province has the potential to generate a large amount of corncob agricultural waste. Corncobs are lignocellulosic residues with a high cellulose content, making them a promising raw material for the production of biodegradable bioplastics. This study aimed to produce and characterize corncob cellulose–based bioplastics combined with chitosan as active packaging to extend the shelf life of food products, particularly pempek. Cellulose was extracted through acid hydrolysis, delignification, alkalization, and bleaching processes, and subsequently formulated into bioplastic films using the solution casting method with varying cellulose concentrations. The bioplastics were characterized in terms of thickness, tensile strength, elongation, biodegradability, and water vapor transmission rate (WVTR). The results showed that increasing cellulose content led to an increase in bioplastic thickness and tensile strength, while elongation and biodegradability decreased. Bioplastic thickness increased from 0.18 mm to 0.25 mm, and tensile strength increased from 0.96 MPa to 7.55 MPa with higher cellulose content. Meanwhile, elongation decreased from 98.6% to 45.21%, and biodegradability declined from 38.91% to 23.61%. In addition, the WVTR decreased to 0.021 g/m²·h at the highest cellulose concentration, indicating improved water vapor barrier properties. These findings suggest that corncob cellulose–based bioplastics with chitosan have strong potential to be developed as environmentally friendly active packaging for food products requiring mechanical protection and moisture control. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 15: Life on Land